Multiple Drug Induced Steven Johnson SyndromeA Case Report - Ragesh, Gurumoorthy; Krishnamoorthy, Nandhini; Sekar, Sarath Kumar (Indian Journal of Pharmacy Practice)
Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are rare, life threatening conditions usually associated with medicines use. They are severe forms of exfoliative dermatitis, and characterized by extensive epidermal erythema and blistering, which leads to necrosis and detachment of the epidermis. They can also cause mucocutaneous lesions.A 28 years old male patient admitted high grade fever associated with chills and rigors and loose stools but not blood stained with Cefotaxim treatment allergic responses like swelling in the B/L legs, rashes with itching followed by skin pealing all over the body, erythema positive on face and hands, multiple painful ulcers in the oral cavity with inflamed borders. Laboratory investigation shown that abnormal values particularly, total count and SGOT (85 U/L), SGPT (108 U/L) levels are elevated abnormally. He is diagnosed as multiple drug induced SJS (Phenytoin, Cefotaxim and native medicines). This case highlights the precipitant of antibiotics for Stevens-Johnson syndrome.
Keywords: Steven Johnson syndrome; Toxic epidermal necrosis; Dermatitis; Epidermis and Erythema